14-Hydroxy-8,14-secogammacera-7-ene3,21-dione from the bark of Lansium domesticum Corr - Supratman, U.; Mayanti, T.; Awang, K.; Mukhtar, M.R.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound (kokosanolide B), C(30)H(48)O(3), the hexahydro- and octahydronaphthalen-2-one ring systems are connected through an ethylene fragment, with a C-CH(2)-CH(2)-C torsion angle of 176.2 (2)degrees. The cyclohexene ring adopts a half-chair conformation, while the other six-membered rings adopt distorted chair conformations. In the crystal, adjacent molecules are linked into a zigzag chain along the b axis by O-H center dot center dot center dot O hydrogen bonds involving the hydroxy and carbonyl groups.